Perencanaan Pertanian Konservasi pada Pengelolaan Lahan Tradisional di Kecamatan Amarasi Barat, Nusa Tenggara Timur: Agricultural Conservation Planning on Traditional Land Management in Amarasi Barat District, East Nusa Tenggara. - Astrid Aryani Ndun; Kukuh Murtilaksono; Dwi Putro Tejo Baskoro; Yayat Hidayat (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Traditional land management system for agricultural activities is carried out throughout the year. It will trigger soil degradation, if it is not accompanied by adequate soil conservation practices. This research aimed to analyze the environmental friendliness of traditional land management systems based on erosion predictions and analyze, plan, and determine appropriate land use planning or conservation measures to increase their environmental friendliness.This research was conducted at three locations representing three traditional land management systems i.emamar system at Teunbaun, slash and burn system at Niukbaun and silvopasture at Merbaun, Amarasi Barat, Kupang, East Nusa Tenggara. This research was conducted in several stages, such as: secondary data collection, observation or primary data collection in the field, laboratory analysis, calculation of erosion factors, prediction of erosion according to the USLE method and recommendations for soil and water conservation measures. The results showed that the slash and burn system had the highest predictive value of erosion (A), namely 2,368.7 ton ha-1 year-1, followed by thewanaternak and mamar system 599.9 to 1,534.5 ton ha-1 year-1. The erosion value (A) can be minimized with conservation measures. Hence the erosion is less than tolerable soil loss (TSL). The recommended conservation action is construction gulud terraces. Crop management that can be done is to increase the density of plant canopy through high agroforesty, crop rotation, and mulching.